PENGARUH BUDAYA PATERNALISTIK TERHADAPKEEFEKTIFAN PENGANGGARAN PARTISIPATIFDALAM PENINGKATAN KINERJAMANAJERIAL PADA BUMN DI PROVINSI ACEH - Waldi Ishaq Siregar (universitas teuku umar, 2020)
The influence of paternalistic culture on the effectiveness of participatory budgeting in improving the managerial performance of BUMN in Aceh propinsi. The purpose of this research is to find out the success of participatory budgeting and its influence with the achievement of managerial work on so-called BUMN companies in Aceh Province. The method used in this study is to use an empirical approach that provides a testing framework to ensure a truth. And to support this research the authors conducted interviews and charging kuisoner to 4 companies and 28 managers in BUMN in the city of Banda Aceh. Based on the results of this research, it was found that participating budget methods and paternalistic cultures in interaction had an influence on the manager's work performance positively indicated by the signification of 0.05. Keywords :Scientific, Management, Business